Enhancing ESL writing using sentence variety checklist - Abdullah, Liza (2014)
One of the students’ problems in writing is lack of variety in sentence structure. Students seem to learn one basic pattern of subject, verb, and object and stick to it. They may also lack knowledge and practice of the different structures, and connecting words, necessary to create sentence variety. Although this is a fundamental problem in student writing, little emphasis has been put on it in the ESL Writing class because oftentimes teachers and students think that as long as there are no grammatical errors in writing, it is “okay.” Therefore, even if students do show some improvement, most of them have not really achieved more desired marks in their writing assessments. Hence, this classroom research intended to examine the respondents’ writing performance before and after using a sentence variety checklist adapted from Langan (1993) and to analyze respondents’ perceptions towards using the sentence variety checklist in their writing. A total of 20 university students in an intensive English language program participated in the study. Data for the study were collected based on students’ essays and responses from a 20-item survey questionnaire. The results revealed slight increase in students’ writing performance in generating complex as compared to simple and compound sentences. In addition, most students found the checklist made writing more interesting and urged them to become more aware of what they were writing. In conclusion, the usage of sentence variety checklist can be one of the tools for ESL students to ‘add more colors’ into their writing. Keywords: ESL writing, sentence variety checklist, sentence structures, sentence combining